The association of HLA-DRB1 alleles and drug use with HIV infection in a Chinese Han Cohort - Diao,Bo (2014)
Objective:To investigate the relationship between the polymorphism of human leukocyte antigen (HLA)-DRB1 and the susceptibility and repellency of drug use combined with HIV infection in Chinese.Methods:A total of 213 unrelated healthy people, 41 HIV-infected drug users, 24 HIV-uninfected drug users, and 64 HIV-infected non-drug users were recruited. Their HLA-DRB1 allele frequencies were analyzed by PCR-SSP and allele distribution was analyzed.Results:Compared with healthy controls, in drug users, the frequencies of HLA-DRB1 *0401-041, *1001 were significantly higher; in HIV-infected patients, the frequencies of HLA-DRB1 *0101-0103, *0401-0411, *1001 were significantly higher, while the frequencies of DRB1 *1501-1502, *1101-1105, *1301-1302, DRB4, DRB5 were significantly lower; in HIV-infected drug users, the frequencies of HLA-DRB1 *0101-0103, *0401-0411, *0801-0806, *1001, *1401/1404/1405 were significantly higher, while the frequencies of DRB1 *1301/1302, 1501-1502, DRB5 were significantly lower.Conclusion:There is close relationship between the polymorphism of HLA-DRB1 alleles and drug use with HIV infection, which plays an important role in elucidating the pathogenesis and providing the basis for therapeutics and prophylaxis of patients with drug use and HIV infection.